ULTRASOUND-ASSISTED TRANSESTERIFICATION OF SOYBEAN OIL USING COMBI-LIPASE BIOCATALYSTS - Freitas,Vitória O. de (2019)
Abstract We applied ultrasonic technology for the transesterification of soybean oil catalyzed by a mixture of lipases (combi-lipase: 75 % Novozym 435; 10 % Lipozyme TL-IM; and 15 % Lipozyme RM-IM), verifying the effects of ultrasonic amplitude, pulse conditions, the ethanol:oil molar ratio, enzyme concentration, and the influence of solvent (tert-butanol on the reaction. We also compared this system against ultrasound combined with mechanical stirring, and the efficiency of the combi-lipase, compared with the individual use of each lipase. The optimum conditions for the transesterification reaction were determined as enzyme concentration of 15 % (in relation to oil mass); ethanol:oil molar ratio of 3:1; ultrasonic amplitude of 30 %, duty cycle of 50 % and time pulse of 15 sec. The yields of conversion of ethyl esters with and without solvent were similar, indicating that the use of solvents during enzymatic transesterification reactions is not necessary when ultrasonic technology is applied to the system. The combination of mechanical stirring and ultrasound did not improve the yields of conversion compared to ultrasonic technology alone. The proposed combi-lipase produced higher yields of ethyl esters (75 %) than the individual lipases (55 %) in 5 h under ultrasonic-assisted batch reactions.